The influence of duration of equilibration, final sperm concentration, and trehalose supplementation on sperm characteristics of Namaqua-Afrikaner spermatozoa - Van Niekerk, Liane (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.